Accumulation of mobility capital over the life course of mobile doctoral candidates. Issue 1 (2nd January 2022) - Schäfer, Gregor
ABSTRACT: Mobility and the expectation of mobility are on the rise for academics, especially in the younger generation of scholars. Career steps in the academic game are very much associated with mobility and spatial flexibility. Current doctoral candidates, who are pursuing their PhD in a country other than their home country, are a good example of this kind of expectation and orientation in an international and mobile academic career. Mobility itself, and the ability to become and be mobile are, however, not free of premises. This paper conceptualizes mobility as a capital that is inherent to its carrier, and asks how this mobility capital is accumulated over the life course of mobile doctoral candidates. The sample includes candidates from Germany who were researching their PhD in France or the Netherlands at the time of the interview. This analysis reconstructs the consecutive steps of the accumulation of mobility capital, shows how it was used to secure the current PhD position and presents different trajectories of accumulation. The impact of supporting institutional environment varies over the life course phases of the person. The findings also show that regardless of the specific trajectory the accumulated mobility capital enabled the doctoral candidate to start his current position abroad.